Comparative Assessment of Microscopy and RDTs in Diagnosing Plasmodium vivax - Mesaulawan, Septyarini; Sorisi, Angle Maria Hasthee; Tuda, Josef Sem Berth (Graha Primera Saintifika, 2025)
Plasmodium vivax is the primary cause of malaria in Indonesia in 2023, particularly in areas with low to moderate endemicity. To reduce malaria transmission, rapid and accurate diagnostic tools are essential for early detection. Microscopic examination remains the gold standard, but the limited availability of trained microscopists and facilities hinders its effectiveness in endemic areas. The Rapid Diagnostic Test (RDT) based on pLDH, such as SD Bioline® Malaria Ag Pf/Pan®, offers rapid results and ease of use, which are beneficial in resource-limited settings. However, performance data for this RDT in Indonesia remains limited. This study evaluates the field performance of SD Bioline® compared to microscopic examination as the reference standard for P. vivax diagnosis. The study involved 62 EDTA blood samples from suspected malaria patients at the Parasitology Laboratory of the Faculty of Medicine, Sam Ratulangi University, from July 2022 to December 2024. Microscopic examination revealed 54 positive cases (87.1%), while SD Bioline® detected 50 positive cases (80.6%). The sensitivity and specificity of SD Bioline® were 92.6% and 100%, respectively, with a negative predictive value (NPV) of 66.6% and a positive predictive value (PPV) of 100%. The results suggest that SD Bioline® demonstrates good sensitivity and specificity for detecting P. vivax in endemic areas. However, false negatives require microscopic confirmation. Combining RDT with microscopy can improve diagnostic accuracy and support Indonesia's malaria elimination efforts by 2030.